Dissolved Organic Phosphorus Production during Simulated Phytoplankton Blooms in a Coastal Upwelling System - Ruttenberg, Kathleen C.; Dyhrman, Sonya T. (Frontiers in Microbiology, 2012)
Dissolved organic phosphorus (DOP) is increasingly recognized as an important phosphorus source that can support primary production in a variety of marine systems. Despite its importance, the production rate and fate of DOP is poorly understood. In this study, four shipboard nutrient addition experiments were conducted during the upwelling summer season off the coast of Oregon (USA) to track DOP production. Nitrogen (N) and phosphorus (P) additions were used to decouple DOP production and hydrolysis by inducing or repressing, respectively, community alkaline phosphatase activity. In order to examine the progression of nutrient uptake and DOP production under upwelling versus relaxation conditions, two experiments were initiated with waters collected during upwelling events, and two with waters collected during relaxation events. Increases in DOP concentration occurred by day-5 in control treatments in all experiments. Nitrogen treatments had increased chlorophyll a, and yielded lower net DOP production rates relative to controls, as well as increased alkaline phosphatase activity, suggesting that DOP levels were depressed as a consequence of increased hydrolysis of bioavailable DOP substrates. Phosphorus additions resulted in a significant net production of DOP at all stations, but no increase in chlorophyll a relative to control treatments. Taken together these data suggest that changes in DIN:DIP will influence DOP production, which in turn may impact the potential export of DOP to offshore ecosystems. A comparison of experimental data from the four sites also suggests that geographic/physiographic conditions exert greater control on DOP production than physical (upwelling versus relaxation) conditions.